2019
DOI: 10.1002/sdtp.12964
|View full text |Cite
|
Sign up to set email alerts
|

35‐4: Color holographic display using quantum‐dot doped liquid crystal

Abstract: We propose the use of a nematic liquid crystal (LC) doped with quantum dots (QDs) to realize a color 3D holographic display. The material has super large optical nonlinearity and could achieve a fast response time ~ 8.46ms. The constructed 3D display shows images at different depths and vivid RGB images at a video refresh rate. Author KeywordsColor holographic display; nematic liquid crystal; quantum dots. Objective and backgroundHolographic display has attracted worldwide attention as a promising three-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Praseetha et al [16] found that CdSe QD doped LC can be considered as a good candidate for the optical limiting application. Wang et al [17] achieved a fast response time in 5CB LC holographic display through using ZnS/InP QD dispersal. Kocakülah et al [18] yielded decreased response time and threshold voltage in polymer stabilized LCs by dispersal of CdSeS/ZnS QDs.…”
Section: Introductionmentioning
confidence: 99%
“…Praseetha et al [16] found that CdSe QD doped LC can be considered as a good candidate for the optical limiting application. Wang et al [17] achieved a fast response time in 5CB LC holographic display through using ZnS/InP QD dispersal. Kocakülah et al [18] yielded decreased response time and threshold voltage in polymer stabilized LCs by dispersal of CdSeS/ZnS QDs.…”
Section: Introductionmentioning
confidence: 99%